An analysis of the prospects and efficiency of floating and overland photovoltaic systems - Khalil Saadaoui; Kaoutar Senhaji Rhazi; Youssef Mejdoub; Abderraouf Aboudou (Institute of Advanced Engineering and Science, 2023)
The world's increasing demand for energy coupled with dwindling natural resources has spurred the need for alternative and renewable energy sources. However, one of the biggest drawbacks of renewable energy is its intermittency. Currently, most of the world's electrical energy comes from thermal power and nuclear energy combined. Despite being heavily reliant on energy imports, Morocco has made progress in developing its solar energy capacity with an installed capacity of 760 MW, 200 MW of which comes from photovoltaics. One way for Morocco to further increase its renewable energy production is through floating solar power, which utilizes the water surface of dams and reservoirs. The challenge with this approach is to secure the floating solar panels to prevent them from being blown about by wind and other elements. Like onshore solar power, offshore solar power also utilizes maximum power point tracking (MPPT) technology to maximize energy production. To compare the efficiency of terrestrial and marine solar power systems, the design and simulation of a solar PV system with MPPT through a boost converter was carried out using MATLAB/Simulink models. The study also examined the impact of water flow characteristics on the output of solar energy from floating panels.